The Influence of Field Experience Practice in Improving the Competence of Teacher Professional Education Students - Ayunin, Qurrota; Fajarianto, Otto (Researchparks Publishing, 2025)
The Teacher Professional Education Program (PPG) is an educational program designed to enhance teachers' competencies in various aspects, including pedagogy, professionalism, social skills, and personality. The Field Experience Practice Program (PPL) is a crucial component of PPG that allows students to apply the theories and knowledge they have learned in real-world settings. This study aims to analyze the impact of the PPL Program on improving the competencies of PPG students. This research is an empirical study of the field experience practices of PPG students, using qualitative methods with data collection techniques including observation, interviews, and documentation. The results of the study show that the PPL Program has a positive influence on improving the competencies of PPG students in various fields. In terms of pedagogy, PPG students demonstrated improved abilities in planning lessons, conducting teaching, and assessing learning outcomes. In the professional aspect, PPG students showed enhanced skills in communication, collaboration, and self-reflection. Socially, PPG students exhibited better adaptation, relationship-building, and leadership abilities. Regarding personality, PPG students displayed increased motivation, commitment, and independence in teaching. The findings of this study indicate that the PPL Program is effective in enhancing the competencies of PPG students. Therefore, efforts should be made to improve the quality and effectiveness of the PPL Program to provide greater benefits for PPG students.